(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Digital marketing refers to any marketing campaign that uses an electronic equipment or the net. Organizations uses digital platforms such as search engines, social media, email, or their website to communicate with current and future consumers. ’Digital advertising,’ ’online marketing,’ or ’internet advertising’ are other terms for it. The advertising of products or services using digital technology, including the Internet, cellular phones, displays marketing, as well as other electronic content, is known as digital marketing. Digital marketing has altered the way brands and businesses use technology for advertising since the nineties or 2000s. As online technologies become increasingly interwoven into marketing tactics and everyday life, and as customers use digital devices instead of visiting physical businesses, digital marketing initiatives are becoming more prevalent and effective. This document concentrates on gaining a conceptual understanding of digital advertising, how it helps today’s organizations, and various case analysis as examples.